Generation of xenobiotic free retinofugal assembloids - Hayes, Michael H.; Valdes Michel, Maria F.; Kuehn, Markus H.; Kardon, Randy H.; Gramlich, Oliver W. (Frontiers in Cell and Developmental Biology, 2026)
Retinal ganglion cells (RGCs) are the output neurons of the retina, responsible for transmitting visual signals to the brain through the optic nerve. Their long axons, high metabolic demand, and the variable environments they transit make them particularly vulnerable to neurodegenerative insults in optic neuropathies. These insults include oxidative stress, excitotoxicity, and inflammatory damage, either within the neuroretina or within the optic nerve, and are thought to drive disease etiology. RGC-related vision loss is the primary presenting concern in many optic neuropathies including glaucoma and autoimmune demyelinating diseases such as multiple sclerosis MS-related optic neuritis (ON) is a result of immune-mediated damage to the myelinated optic nerve, a process not fully recapitulated in current in vitro organoid models. For instance, 3D organoid models offer improved architectural context, but they lack crucial cell types and sufficient anatomic complexity to mimic the in vivo environment. Further, widespread use of animal-derived reagents in these systems can introduce significant phenotype variability posing a major barrier to translational research. To address these challenges, retinofugal assembloid models have emerged. These models combine retinal and brain organoids to recapitulate the in vivo visual pathway, supporting RGC survival, RGC axonal extension and pathfinding, incorporation of additional glial cell types, and provide sufficient complexity. Here, we describe xenobiotic-free protocols for generating retinal and oligodendrocyte-rich cortical organoids and their fusion into assembloids to more accurately model RGC physiology. We discuss the advantages, limitations, and future applications of these systems in studying neuroinflammation and demyelination in a human-relevant context.